马拉拿达基督教高中二年级理科班学生对词汇的掌握情况分析 - Irvan Irvan; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2019)
AbstractVocabulary is very important for classroom teaching and improving students language ability. We also need enough vocabulary to express information clearly. Classroom teaching usually starts with vocabulary. Students often encounter difficulties in learning vocabulary, especially the meaning and usage of words. In this case, in order to understand students vocabulary acquisition in learning, the author does research on the second-year science class of Christian High School in Maranatha. The author carries on the test, through the test paper to analyze and statistics the test results. After the research, the author draws a conclusion that, on the whole, the students have the best mastery of Chinese vocabulary, monosyllabic vocabulary, followed by disyllabic vocabulary, and vocabulary usage is not good. Keywords: Vocabulary, Vocabulary Teaching, Mastery